Preoperative period as a stressful situation for women - Pilewska, Anna; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2005)
Aim of study: The aim of the study was to verify, whether and how far preoperative period was stressful situation for women hospitalized in gynaecology department. Materials and methods: The study was carried out among 200 patients with gynaecological illnesses operated in Departament of Reproduction and Andrology Skubiszewski Medical University of Lublin. The study was carried out on the basis of author’s questionnaire interview and analyses of medical history. Moreover Numerical Scale (0–10, normally used for pain estimation) was used for self-evaluation of stress. Results: The majority of respondents (93%) said that the operation was planned. A great majority of women (95.5%) expressed their anxiety as regards hospitalization. The mean value of a level of stress in preoperative period was 6.3±0.18 points in the patients self-evaluation and after operation it was 4.07±0.18. The majority (90.0%) of patients admitted they had needed support while awaiting the surgery. Conclusions: Hospitalization and surgery treatment disturbed a great rhythm of life in opinion nearly third of woman. A great majority of patients expressed their anxiety with relation to surgery intervention. The reason of anxiety was: the convalescence, pain, anaesthesia. Higher level of stress was found in the patients before operation than during postoperative period. The majority of respondents expected some support. More than half of women were willing to participate in support group for patients prepared for operation.